Use of implants for management of the anophthalmic socket - Oria, A. P.; Dorea Neto, F. A.; Gomes Junior, D. C. [UNESP]; Pinna, M. H.; Laus, J. L. [UNESP] (Univ Federal Rural Pernambuco, 2011)
The implants are usually used after removal of the eye or its internal content, in order to maintain the orbital volume or, as in medicine, provide also the subsequent placement of ocular prosthesis. Considering prosthetic surgery procedures of high relevance in human and veterinary ophthalmology, this paper seek to review the main types of implants described in national and international literature, as well as describe the main complications when they are used in humans and veterinary patients.
Keywords: Ocular implants; enucleation; biomaterials